Pengaruh Model Two Stay Two Stray Terhadap Hasil Belajar Bahasa Indonesia Kelas V SDN Gugus XI - Gufita, Nurma; Yuliantini, Nani; Dalifa (JURIDIKDAS, 2025)
The objective of this research is to explore how the cooperative learning approach known as "Two Stay Two Stray" affects the academic performance of fifth-grade students in Cluster XI Elementary Schools regarding their Indonesian language proficiency. This investigation employs a matched pretest-posttest control group design. The study encompassed all fifth-grade students attending SDN Cluster XI in Bengkulu City as its population. The experimental group consisted of fifth-grade students from SDN 44 Kota Bengkulu, while the control group comprised fifth-grade students from SDN 55 Kota Bengkulu. Data collection involved pretest and posttest assessments using objective test instruments. Descriptive statistics and inferential analysis, specifically the t-test, were employed for data analysis. The findings revealed a significant contrast in posttest scores between the experimental and control groups, as evidenced by the t-value (2.263), which surpassed the critical t-value (1.697). It may be concluded that the "Two Stay Two Stray" cooperative learning approach had an effect on the Indonesian language learning outcomes of fifth-grade students at SDN Cluster XI in Bengkulu City by rejecting the null hypothesis (H0) and adopting the alternative hypothesis (Ha). This conclusion is drawn from the differing treatments applied to the control and experimental groups